Establishment of human umbilical cord-derived mesenchymal stromal cells expressing interleukin-12 and assessment of their effect on lung adenocarcinoma cells - Goh, Jiunn Jye (2023)
Mesenchymal stromal cells (MSCs) are promising vehicles for cancer therapy due to their homing ability. They can be genetically manipulated through either non-viral or viral methods to express anti-cancer genes for cancer therapy. Interleukin-12 (IL-12) is one of the key immunomodulatory cytokines which has potential in antitumour effect. However, systemic administration of the cytokine at therapeutic dosage can lead to serious toxicity in the host system due to the high systemic level of interferon-γ (IFN-γ) induced by this strategy. In this study, we investigated the in vitro growth inhibition of genetically engineered human umbilical cord-derived mesenchymal stromal cells (hUCMSC) expressing IL-12 on human lung adenocarcinoma cells. The hUCMSC-IL12 were generated via adenoviral and electroporation method. Based on the results between the two methods, adenoviral method showed superior results in transfection efficiency (63.6%), post-transfection cell viability (82.6%) and hIL-12 protein expression (1.2 x 107 pg/ml). Thus, adenoviral vector was selected for the downstream experiments. Subsequently, hUCMSC-IL12 showed significant inhibition effect on H1975 lung adenocarcinoma cells after 5 days of co-culture. No significant difference was observed for all other co-culture groups, indicating that the inhibition effect was because of hIL-12. Interestingly, cell viability of MRC-5 cells was significantly increased on day 5 after co-cultured with untransduced hUCMSC but not hUCMSC-IL12. The hIL-12 mRNA was upregulated significantly in hUCMSC-IL12 compared with untransduced hUCMSC leading to the exogenous expression of hIL-12 protein in the supernatant of hUCMSCIL12. The hIL-12 protein expressed by hUCMSC-IL12 was 1.2 µg/ml on day 3 and increased to 2.2 µg/ml on day 5. Lastly, the integrity of hUCMSC-IL12 remained unaffected by the transduction through examination of their surface markers and differentiation properties. In conclusion, this study provided the proof of concept that hUCMSC can be genetically engineered to express hIL-12 and exert growth inhibition effect on human lung adenocarcinoma cells.